Restoration of renal function in patients with newly diagnosed multiple myeloma is not associated with improved survival: a population-based study. Issue 9 (2nd September 2017) - de Vries, Joost C.; Oortgiesen, Berdien; Hemmelder, Marc H.; van Roon, Eric; Kibbelaar, Robby E.; Veeger, Nic; Hoogendoorn, Mels
Abstract: Renal impairment (RI) in patients with multiple myeloma (MM) is associated with poor prognosis. In this population-based cohort study, we assessed the effects of renal response, evaluated according to the IMWG-criteria, on overall survival (OS) in patients with newly diagnosed MM with RI at presentation. All included patients were diagnosed between January 2005 and January 2014 with MM and RI in Friesland, a province of the Netherlands. Of the 131 included patients, 61% achieved renal response. Using a time-varying exposure Cox model, no difference in OS between renal response and non-response was observed (HR = 1.08, 95% CI = 0.67–1.74, p  = .76). In multivariable analysis, baseline eGFR <30 ml/min (HR = 1.71), age >70 yrs (HR = 1.77), hypercalcemia (HR = 2.73), lambda Bence–Jones (HR= 1.76), and initial treatment regimen (HR = 0.89 for thalidomide, HR = 1.95 in treatment regimens without novel agents and HR = 3.60 for no chemotherapy, all vs. bortezomib) were associated with decreased OS. In conclusion, achieving renal response was not associated with improved OS.